2015
DOI: 10.1073/pnas.1505317112
|View full text |Cite
|
Sign up to set email alerts
|

Identification of divergent type VI secretion effectors using a conserved chaperone domain

Abstract: The type VI secretion system (T6SS) is a lethal weapon used by many bacteria to kill eukaryotic predators or prokaryotic competitors. Killing by the T6SS results from repetitive delivery of toxic effectors. Despite their importance in dictating bacterial fitness, systematic prediction of T6SS effectors remains challenging due to high effector diversity and the absence of a conserved signature sequence. Here, we report a class of T6SS effector chaperone (TEC) proteins that are required for effector delivery thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
186
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(208 citation statements)
references
References 64 publications
9
186
0
2
Order By: Relevance
“…5A), we hypothesized that in addition to VgrG1, Atu4349 and Atu4352 may play roles in Tde1 translocation. This hypothesis was indeed supported by our previous observation that the DUF4123-domain-containing protein Atu4349 interacts directly with Tde1 to form a complex in E. coli and stabilizes Tde1 in A. tumefaciens C58 (6), and two recent studies identifying a V. cholerae DUF4123-domain-containing protein, Tap-1/Tec, required for loading a specific effector onto cognate VgrG for secretion (32,33). Thus, we first determined the role of atu4349 (named tap-1) and atu4352 (named paar) in Tde1 secretion and Tde1-dependent antibacterial activity.…”
Section: Domain Dissection Of Vgrg In Type VI Secretion and Tde Toxinsupporting
confidence: 60%
See 3 more Smart Citations
“…5A), we hypothesized that in addition to VgrG1, Atu4349 and Atu4352 may play roles in Tde1 translocation. This hypothesis was indeed supported by our previous observation that the DUF4123-domain-containing protein Atu4349 interacts directly with Tde1 to form a complex in E. coli and stabilizes Tde1 in A. tumefaciens C58 (6), and two recent studies identifying a V. cholerae DUF4123-domain-containing protein, Tap-1/Tec, required for loading a specific effector onto cognate VgrG for secretion (32,33). Thus, we first determined the role of atu4349 (named tap-1) and atu4352 (named paar) in Tde1 secretion and Tde1-dependent antibacterial activity.…”
Section: Domain Dissection Of Vgrg In Type VI Secretion and Tde Toxinsupporting
confidence: 60%
“…One is PAAR protein, which interacts directly with the last β-strand of a gp5-VgrG chimera and can act as an adaptor between VgrG and effector to facilitate secretion of a broad range of T6SS toxins (28). Others include the DUF4123-domain-containing protein Tap-1/Tec for loading a specific effector onto cognate VgrG for delivery in V. cholerae (32,33) and EagR accessory protein specifically required for deployment of its associated Rhs effector in Serratia marcescens (8). We found that all tde1 orthologs are linked to an upstream tap-1, and except for in I. limosus, are associated with a downstream paar gene (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously characterized the T6SS antibacterial activities of two waterborne pathogens, Vibrio cholerae strain V52 (13) and Aeromonas hydrophila strain SSU (21). V. cholerae possesses four antimicrobial effectors, namely, VgrG3, which functions as a lysozyme (13,22); the lipase TseL (13,23); VasX, which has a colicin-like domain (13,24); and the hydrolase TseH (25), which seems to play only a minor role in interbacterial killing (25).…”
mentioning
confidence: 99%